Analisis Pengaruh Kompensasi, Kepemimpinan Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Muhammad Afif (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aimed to describe the compensation, leadership and work environment on employee job satisfaction at a McDonald's restaurant in the city of Malang. Examine the effect of compensation, leadership and work environment on employee job satisfaction and analyze which of the variable compensation, leadership and work environment the dominant influence on employee job satisfaction. To reach this objective, the research method used was survey method in which the collection of information from respondents was conducted using questionnaires and calculations using SPSS. The population in this study are employees of McDonald's restaurants in Malang, amounting to 98 people. This study uses data subjects, namely in the form of a written response from the respondent with regard to grains have a question or statement made as one from each of the indicators in each variable. For the source of this research is the primary data source